1989
DOI: 10.1152/ajpcell.1989.257.6.c1069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cysteine protease inhibitors on rabbit cathepsin D maturation

Abstract: To examine the effects of cysteine protease inhibitors on cathepsin D intracellular transport, proteolytic processing, and secretion, primary cultures of rabbit cardiac fibroblasts were grown to confluence and exposed (24 h) to media containing leupeptin (0-10 mM), E 64 (0-10 mM), or chloroquine (0-50 microM). Cathepsin D maturation was then evaluated in pulse-chase biosynthetic labeling experiments. None of the three agents affected the charge modification of procathepsin D (Mr 53,000) within the Golgi appara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…14 Cathepsin C is activated early in the endocytic pathway by other lysosomal enzymes, such as cathepsin D. 14,16,47 We have shown that the cathepsin D inhibitor, pepstatin b, specifically blocks LLOMe-induced cell death, but not pyroptotic cell death (Fig. 1B).…”
Section: Llome-mediated Cell Death Is Controlled By Cathepsin Dmentioning
confidence: 94%
“…14 Cathepsin C is activated early in the endocytic pathway by other lysosomal enzymes, such as cathepsin D. 14,16,47 We have shown that the cathepsin D inhibitor, pepstatin b, specifically blocks LLOMe-induced cell death, but not pyroptotic cell death (Fig. 1B).…”
Section: Llome-mediated Cell Death Is Controlled By Cathepsin Dmentioning
confidence: 94%
“…Lysosomal and vacuolar proteinases are representatives of the second type. Human procathepsin D is capable of only partial self processing and activation [30,31] requiring lysosomal cysteine proteinase(s) for the final processing of its pro-part [32]. Similarly, serine vacuolar proteinase B is responsible for the final proteolytic maturation of the zymogen of proteinase A of yeast [33].…”
Section: Mode Of Processingmentioning
confidence: 99%
“…Further proteolytic cleavage that does not result in dissociation of CD globular structure yields the mature active lysosomal protease which is composed of heavy (34 kDa) and light (14 kDa) chains linked by non-covalent interactions [11][12][13]. Cysteine proteases and autocatalytic activity of CD is most-likely involved in pCD/CD processing [14][15][16][17]. Several factors were found to affect CD activation including a lipid second mesenger ceramide and prosaposin [10,18].…”
Section: Introductionmentioning
confidence: 99%